2015
DOI: 10.1016/s2095-3119(15)61033-4
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of tribasic zinc sulfate for broilers fed a conventional corn-soybean meal diet

Abstract: An experiment was carried out to investigate the relative bioavailability of tribasic zinc (Zn) sulfate relative to Zn sulfate for broilers fed a conventional corn-soybean meal diet. A total of 504 one-day-old Arbor Acres commercial male chicks were randomly assigned by body weight of birds to one of seven treatments involving a 2×3 factorial arrangement with three levels of added Zn (30, 60, or 90 mg of Zn kg-1) and two Zn sources (tribasic Zn sulfate and Zn sulfate) plus a control with no added Zn for an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In our laboratory, the multiple linear regression slope ratio method has been successfully used for estimating Fe, Mn, and Zn bioavailabilities of Fe, Mn, and Zn sources for broilers under conventional corn-soybean meal diets (Li et al, 2015;Suo et al, 2015;Zhang et al, 2016). Similarly, it is reported in other studies that Se-enriched yeast were more efficient in maintaining the GSH-Px activity level than SSe (Payne and Southern, 2005).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In our laboratory, the multiple linear regression slope ratio method has been successfully used for estimating Fe, Mn, and Zn bioavailabilities of Fe, Mn, and Zn sources for broilers under conventional corn-soybean meal diets (Li et al, 2015;Suo et al, 2015;Zhang et al, 2016). Similarly, it is reported in other studies that Se-enriched yeast were more efficient in maintaining the GSH-Px activity level than SSe (Payne and Southern, 2005).…”
mentioning
confidence: 69%
“…The bioavailability of trace minerals is defined as the degree to which an ingested element in a particular source is absorbed, transported to its site of action, and converted to a physiologically active form that can be used in metabolism by the animals (Ammerman et al, 1995;Li et al, 2015). Therefore, the sensitive criteria should be selected for estimating the relative bioavailability of Se in USSe.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Zn content in these tissues can accurately reflect the differences in Zn absorption and utilization from different Zn sources and levels. Plasma and pancreatic Zn concentrations increased linearly as dietary Zn concentration increased in Zn sulfate source at 6 or 14 d of age in broilers (Li et al, 2015). Tang et al (2015) found that Zn-bearing zeolite clinoptilolite supplementation to diets increased Zn accumulation in liver and tibia of birds compared with diet with Zn in broilers.…”
Section: Discussionmentioning
confidence: 99%